2002
DOI: 10.1006/icar.2001.6804
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Behavior of Stratospheric Ammonia Abundance and Temperature Following the SL9 Impacts

Abstract: Infrared emission lines of stratospheric ammonia (NHwith cold jovian air. During the first 4 days after impact, NH 3 was present primarily at altitudes above 1 mbar with a column density of (7.7 ± 1.6) × 10 17 cm −2 after 1 day and (3.7 ± 0.8) × 10 17 cm −2 after 4 days. (Errors represent precision.) We obtained >2.5 times more NH 3 than can be supplied by nitrogen from a large cometary fragment, suggesting a primarily jovian source for the NH 3 . By 18 days postimpact, a return to quiescent upper stratospheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
4
10
0
Order By: Relevance
“…They interpreted these two NH 3 components as representing, respectively, upwelling of jovian air from the troposphere, and plume deposition. Building upon a preliminary report by Kostiuk et al (1996), Fast et al (2002) found a timevarying vertical profile of NH 3 in site G, with NH 3 restricted to p < 1 mbar 1-4 days after impact but extending down to the 50 mbar level at t + 18 days, and reached similar conclusions for impact K 4 and 7 days after impact. However, unlike Griffith et al (1997), they found comparable amounts of NH 3 in the two components.…”
Section: Comparison With Previous Measurements and Evolution Of The Hsupporting
confidence: 62%
“…They interpreted these two NH 3 components as representing, respectively, upwelling of jovian air from the troposphere, and plume deposition. Building upon a preliminary report by Kostiuk et al (1996), Fast et al (2002) found a timevarying vertical profile of NH 3 in site G, with NH 3 restricted to p < 1 mbar 1-4 days after impact but extending down to the 50 mbar level at t + 18 days, and reached similar conclusions for impact K 4 and 7 days after impact. However, unlike Griffith et al (1997), they found comparable amounts of NH 3 in the two components.…”
Section: Comparison With Previous Measurements and Evolution Of The Hsupporting
confidence: 62%
“…2d). Ammonia emission from the stratosphere was previously only observed in the aftermath of the SL9 impacts (Kostiuk et al, 1996;Griffith et al, 1997;Fast et al, 2002).…”
Section: N-band Spectramentioning
confidence: 97%
“…However, the same experiments with the absolutely calibrated N-band spectra produced the same conclusion. The best reference profile used a decaying NH 3 mole fraction with altitude, rather than the constant vertical profiles of Fast et al (2002). This profile is physically realistic, as it represents the decreasing photochemical lifetime with altitude as UV shielding becomes less efficient.…”
Section: Determining the Nh 3 Reference Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, slow upwelling of tropospheric air (responsible for the presence of NH 3 in the stratosphere in both SL9 and the 2009 impacts, Griffith et al 1997;Fast et al 2002;Fletcher et al 2010) could have raised this newly-produced ethane into the lower stratosphere. But given that the small tropospheric abundance of C 2 H 6 (approximately 0.7 ppm at 200 mbar at 50 • S, Nixon et al 2007) is smaller than the quantities detected over the impact streak, some excess production of C 2 H 6 must have occurred.…”
Section: Hydrocarbon Enhancements Over the Impactmentioning
confidence: 99%